(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يعد أفيوليت البولكاليزا في جنوب بولونيا/جبال سوفيه/ جزءاً من الحزام الأفيوليتي النيو-تيتسي حيث يعد امتداداً لأفيوليت الكاربات والأفيوليت السلوفاكي. وكما هو الحال في العديد من التتابعات الأفيوليتية المرتبطة بهذا الحزام فإن أفيوليت البولكاليزا يحتوي على صخور الغابرو، والتي تشبه مثيلاتها في المعقد الأفيوليتي السوري في البسيط، مع بعض الفروقات المحلية، وعلى الرغم من أنها من مناطق مختلفة من الأحزمة الأفيوليتية ومن عمرين مختلفين لكن يعتقد أنها جميعاً تشكلت كنتيجة لعمليات تشكل محيط التيتس وتطوره واختفائه. الصخور المدروسة في هذا البحث عبارة عن الغابرو ، ونتيجة للدراسات البتروغرافية-الفلزية نميز بين نوعين من صخور الغابرو من حيث حجوم الحبات :غابرو متوسط حجوم الحبات ، وغابرو-بازلت ناعم الحبات مع بعض الميغاكريست من البلاجيوكلاز والبيروكسين. لدراسة التركيب الفلزي استخدمنا المجهر الإلكتروني لإجراء العديد من التحاليل الكيميائية النقطية للفلزات. The Ophiolite of Polkalesia in southern Poland, Sowie Mountain, is part of the New-Tethyan Ophiolite northern belt, where it is regarded as a continuation of Carpathian and Slovakian Ophiolite. As is the case with many of the ophiolite occurrences in this belt, the sequences are closely associated with this belt, polkalesia ophiolite contain gabbro rocks, which are similar to gabbro of the Syrian ophiolite in Al-Bassit area, with some local differences. Despite the fact that they belong different places of ophiolite belts and are of different ages, they are thought to be formed as a result of formation and development processes, and the disappearance of the Tethys Ocean. The studied rocks in this research are gabbros. In the light of petrography studies and by relying on the size of grains, we can distinguish two types of gabbros: those of medium-size grains and fine basalt-gabbro with megacryst of plagioclase and pyroxenes. Studying mineral composition, we have used an electronic microscope to conduct microprobe analyses of minerals.